Question
upstudy study bank question image url

12:13 5G 12 siyavula.com Siya \( \sqrt{4} / 2 \) The other factor of \( x^{2}+b x+24 \) is: \( x+6 \) \( x-6 \) \( (x+b)+24 \) Impossible to find Exactly right. High five! Show the full solution 2. Consider the same equation: \[ x^{2}+b x+24=0 \] Use your answers to Question 1 to determine: 1. The other solution to the equation. 2. The value of \( b \). 95

Ask by Gibson Bowman. in South Africa
Feb 08,2025

Real Tutor Solution

Tutor-Verified Answer

Answer

1. The other solution to the equation is \( x = -6 \). 2. The value of \( b \) is 10.

Solution

We start with the quadratic:   x² + bx + 24 = 0 Suppose that in Question 1 you found one of the factors to be (x + 4). (This is consistent with the fact that factors of 24 that add up to give b in the factored form are 4 and 6.) To factor the quadratic completely, we need to find the other factor, say (x + c), such that   (x + 4)(x + c) = x² + bx + 24. Step 1. Expand the product:   (x + 4)(x + c) = x² + (4 + c)x + 4c. Step 2. Compare coefficients with x² + bx + 24:   • The constant term: 4c = 24 ⟹ c = 6.   • The coefficient of x: 4 + c = 4 + 6 = 10, so b = 10. Thus, the factorization is:   x² + 10x + 24 = (x + 4)(x + 6). Step 3. Find the solutions: Set each factor equal to zero.   x + 4 = 0 ⟹ x = –4,   x + 6 = 0 ⟹ x = –6. Since you already had one solution (x = –4), the other solution is x = –6. Summary of Answers: 1. The other solution of the equation is x = –6. 2. The value of b is 10.

Reviewed and approved by the UpStudy tutoring team

error msg
Explain
Simplify this solution

The Deep Dive

Let’s dive into the world of quadratic equations! The equation \( x^{2}+b x+24=0 \) can be factored using the known root \( x+6 \). Using Vieta’s formulas, which relate the coefficients of the polynomial to sums and products of its roots, we find the other root can be determined since the product of the roots must equal 24. If one root is -6, then the other root must be 4 because \(-6 \times 4 = -24\). So, you've got that value! Now, to find \( b \), we use the sum of the roots, which, according to Vieta’s, is equal to -b. Adding your roots (-6 and 4) gives us -2, thus \( b \) must be 2. So, your final values are \( b = 2 \) and the other solution is 4. High five again for cracking the code!

Try Premium now!
Try Premium and ask Thoth AI unlimited math questions now!
Maybe later Go Premium
Study can be a real struggle
Why not UpStudy it?
Select your plan below
Premium

You can enjoy

Start now
  • Step-by-step explanations
  • 24/7 expert live tutors
  • Unlimited number of questions
  • No interruptions
  • Full access to Answer and Solution
  • Full Access to PDF Chat, UpStudy Chat, Browsing Chat
Basic

Totally free but limited

  • Limited Solution
Welcome to UpStudy!
Please sign in to continue the Thoth AI Chat journey
Continue with Email
Or continue with
By clicking “Sign in”, you agree to our Terms of Use & Privacy Policy